Strategic Management by Enterprise’s Transport Potential - Kulakova, Svitlana; Boldyrieva, Lyudmyla; Ðmelina, Iryna; Goloborodko, Alexander (International Journal of Engineering and Technology, 2018)
Two methods of determining the structure of transport potential are proposed: cost and energy. The aim of the research is to study the economic assessment of the transport potential components and its structure should be carried out taking into account certain strategic principles: probability, accuracy and scientific validity of the transport potential structural components, comparability of the transport potential structural components, temporal comparability of the transport potential, comparability of the transport potential by the range of the objects under analysis. It is proved that transport potential (TP) is expedient to determine how the amount of transport works that can be performed at the standard use of the enterprise’s transport resources (transport unit) for according to a certain period. It is proved that transport potential is characterized by both stability and volatility. It is determined that the increase of transport potential value has the following limitations: imperative of life safety (growth of transport potential should not worsen working conditions and create threats to people’s health); ecological imperative (increasing the volume of transport potential should not cause the complication of the environmental situation and damage the environment).This research reflected that transport resources can be attributed to the primary potential factors.The mechanism for motivating the effective use of transport resources is being implemented. The mechanism includes detection of reserves for reducing the transport volume of products, development of measures on the use of certain reserves for reducing the transport volume of products. Implementation of measures for realization of detected reserves is done reduces the transport volume of products, reducing transport capacity products, and rewarded for reducing the transport capacity of products.